The Roles and Interplay of Intragroup Conflict and Team Emotion Management on Information Seeking Behaviors in Team Contexts - Meng, Jingbo and Fulk, Janet and Yuan, Y. Connie (Communication Research, 2015)
This study developed a cross-level model to study the effects of contextual factors, including team-level conflict and team-level emotion management (EM), on how individual team members seek information. Cross-level analysis using data collected from 175 individuals in 30 teams showed that team-level relationship conflict (TRC) had a negative effect on individual information seeking (IS) behavior, whereas team-level task conflict (TTC) did not have a significant effect. EM at both team and individual levels had positive effects on individual IS behavior. The same set of analyses conducted using a subset of 22 of these teams at an earlier time point confirmed the same pattern of relationships. In addition, team-level EM interacted with TRC in influencing individual IS behavior, although the patterns varied for the two time points of data collection. Theoretical implications are discussed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjEzNDc2Mjk0